Autorzy:Janowicz Jerzy
Wydawnictwo:Nowa Era
Rok wydania:2015
Wykonaj redukcję wyrazów podobnych 4.43 gwiazdek na podstawie 7 opinii

`a)\ ul(9m)+ul(ul(14k))-ul(6m)-ul(ul(6k))=3m+8k` 

`b)\ ul(13x^2)-ul(ul(15x))-ul(11x^2)+1+ul(ul(14x))+20=` `2x^2-x+21` 

`c)\ ul(-4xy)+ul(ul(8x))-ul(ul(ul(y)))+ul(ul(21x))-ul(ul(ul(9y)))-ul(xy)+5=` `-5xy+29x-10y+5` 

`d)\ ul(1/3m^2k)+ul(ul(5,2mk^2))-9mk+ul(2 2/3km^2)-ul(ul(9,4k^2m))=` `3km^2-4,2k^2m-9km` 

`e)\ ul(0,33x^3y^4)-ul(ul(0,22x^4y^3))-0,11xy^4+ul(0,77x^3y^4)+ul(ul(0,88x^4y^3))=` `1,1x^3y^4+0,66x^4y^3-0,11xy^4`